Royal Ms 20 D ii Tristan (AM Scholar: Medieval and Early Modern Studies., 2019)
Description: TRISTRAM: second part of the French prose romance in the enlarged version purporting to be by Hélie de Borron, see Ward, Cat. of Romances, i, pages 361. For an analysis of the romance, based on the Paris MSS., see E. Löseth, Le Roman en Prose de Tristan, Bibliothèque de l'École des Hautes Études, Sciences Phil. et Hist., fascicle 82 (1890). It is probable that a single leaf (distinct from the first gathering, perhaps because it included a larger miniature) has been lost at the beginning, compare Add. MS. 5474. The MS. at present begins 'Or dit li contes que quant li rois Marc ot abatu monsengnor Y[uein] as blanches meins', and the text of the earlier part (ff. 2-l0l, corresponding to Löseth, [][] 171-282) seems to have some affinity with the Paris MS., Bibl. Nat., fonds fr. 335, 336. The passage following ([] 338 b) corresponds nearly to Paris MS. 755, but none of Löseth's MSS. seem to agree very closely with this. The MS. ends ([] 571) 'et de la furent trouees a porter premierement robes noires. Explicit'. Colophon, 'Ci faut li romanz de Tristran et diseult la b[l]onde de Cornoalle'. At the top of the last leaf (f. 315) a few lines are torn from each column. On the fly-leaf are (a) Verses on prognostication for the year from the 1st of January attributed here to the prophet Ezekiel, see 12 C. XII, art. 27, but the texts differ greatly. Beg. 'En terre de labour et de promission'. In a band of the middle of the 14th century f. 1;-(b) Rondeau, in a 15th century hand, beg. 'De bien seruir a mon pouoir | Ie feray mon leal deuoir'. f. 1 bornVellum; following 315. 131/4 in. x 91/4 inches Written in France, circ. A.D. 1300. Gatherings (beg. f. 2) of 8 leaves (x10, xii10, xxiv2, xxvii7, xxviii6, xxxix10, last4), with catchwords. Double columns. Sec. folio 'a Adret' (but originally 'Or dit' ?). Illuminated initials, sometimes (e.g. following 139 b, 146 b) with bar-prolongations in the border, and in the case of the opening of sections (58 in number) with small miniatures of knights, andc., rather poorly executed. A 15th century owner's name on f. 1 b is G. Hermanuille and there is also a doggerel rhyme 'Charles de Hermanuille vint | sua vn cheual qui valloit vint. | Vn vol de chiunc (?) sus son heaume | Bien sanbloit sire dun roieaume'. In a very similar hand is written 'Cest liure cy est a Gorge Nessefeld'. The MS. belonged, also in the 15th century, to [Admiral] Prigent de Coëtivy, whose autograph signature and mottoes, 'a belle merciis' and dame sans per', are on f. 1 born Cf. Lansdowne MS. 1179, and see L. Delisle, 'Les Heurca de l'Amiral Prigent de Coëtivy', in Bibl. de l'École des Chartes, lxi (1900), pages 186, and H. Yates Thompson, Descriptive Cat. of the 2nd Ser. of Fifty MSS. (19O2), pages 238. This cannot be the copy of Tristram mentioned by Delisle as executed for the Admiral by Jean Haincelin, but may have been used for Haincelin to copy from. Another owner, still of the 15th century, is Kirkeby (f. 1 b, with motto 'entier en tout', and following 112 b, 113, compare '[Eli]zabeth Kykeby', f. 315 b). Cat. of 1666, f. 13; not in CMA.